PENGARUH HUTANG TERHADAP LABA USAHA PADA PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Repi Lesmana Dewi; Maliah Maliah (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
This study aims to determine whether there is an effect of short-term debt (CL) and long-term debt (NCL) on operating income (OP) in consumer goods companies listed on the Indonesia Stock Exchange either partially or simultaneously. The formulation of the problem in this study is: Does the variable Short-Term Debt and Long-Term Debt have a significant effect either partially or simultaneously on Operating Profit of consumer goods companies listed on the Indonesia Stock Exchange. This study uses data from the 2016 to 2018 Financial Statements. In this study, the sample was taken using the non-probability sampling method, which does not provide equal opportunities for each member of the population to be selected as samples. while the sample selection was carried out using the purposive sampling method, namely a sampling technique with special considerations so that it was appropriate to be a sample, by determining the number of samples as many as 20 samples, so that the research data derived from the 2016 to 2018 financial statements were 60 data. The data collected is secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id (Indonesian Stock Exchange Investment Gallery) Musi Charitas Catholic University Palembang, Faculty of Business and Accounting. The method used in this study is a quantitative method which is a quantitative method. associative method with the form of a causal relationship. The analysis technique used is Multiple Linear Regression Analysis. The results of this study indicate that partially short-term debt (CL) has no significant effect on operating income (OP), long-term debt (NCL) has a significant effect on operating income (OP). Simultaneous results show that short-term debt (CL) and long-term debt (NCL) have a significant effect on operating income (OP).Keywords: Short-Term Debt (CL), Long-Term Debt (NCL), Operating Profit (OP).